Risk of tuberculosis infection among health care workers and nursing students in Japan. Issue 11 (November 2018) - Nishimura, Tomoyasu; Ota, Masaki; Mori, Masaaki; Fujiwara, Hiroshi; Takano, Yaoko; Kato, Seiya; Kawabe, Hiroshi; Hasegawa, Naoki
Abstract: It is important to evaluate the risk of tuberculosis (TB) infection among health care workers (HCWs) and nursing students in Japan to propose the optimal countermeasure against new TB infection for them. To estimate the annual incidence of TB infection in HCWs at a Japanese university hospital without TB wards and in nursing students at a Japanese university using interferon-gamma release assay (IGRA). Serial IGRAs were prospectively conducted on the HCWs between August 2010 and December 2015. For nursing students, two IGRA tests were conducted before commencement of clinical training and at employment as nurses between April 2007 and December 2015. A total of 328 HCWs and 298 nursing students were followed for 670.15 and 1212.80 person-years, respectively. Assuming IGRA-positive conversions were all attributable to true infection, the incidence of TB infection in HCWs and nursing students was 0.149/100 and 0.0825/100 person-years, respectively. At a Japanese university hospital without TB wards and a Japanese university, the annual incidence of TB infection among HCWs and nursing students estimated from serial IGRA results was low, but continued vigilance for the prevention of TB infection is essential.